IMPLEMENTASI SUPERVISI PENDIDIKAN DALAM PENINGKATAN MUTU PEMBELAJARAN - Istiqomah (PT. Saha Kreasi Indonesia, 2026)
This study examines the implementation of educational supervision in improving learning quality based on previous research findings. A library research approach was employed by analyzing academic books, national and international journal articles, and other relevant studies. Data were analyzed using content analysis through the stages of data reduction, organization, and synthesis. The findings indicate that educational supervision functions as an effective professional development mechanism to enhance teachers’ pedagogical competence, particularly in lesson planning, instructional implementation, and learning evaluation. Supervision that is systematically planned, collaboratively implemented, and continuously followed up encourages reflective teaching practices and supports ongoing improvement in classroom instruction. The effectiveness of supervision is influenced by supporting factors such as leadership commitment, supervisor competence, teachers’ openness to feedback, and a collaborative school culture, while inhibiting factors include time constraints, administrative workload, and insufficient follow-up. Therefore, educational supervision plays a strategic role in improving learning quality when it is positioned as a reflective and sustainable professional development process rather than merely as an administrative control activity.